STRATEGI PEMASARAN BAKSO TITOTI CABANG KOTA BEKASI SELAMA PANDEMI COVID 19: MARKETING STRATEGY OF TITOTI MEATBALL BRANCH BEKASI CITY DURING THE COVID 19 PANDEMIC - Rahmanto, Muhammad Ikhwan; Listyowati, Esi Asyani; Aditya, Dwi; Danapriatna, Nana (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2023)
Meatball stalls are a culinary business that has many fans in many places, including Bekasi City. A culinary phenomenon with a unique appeal is an interesting theme to research. This study aims to determine the internal and external environmental factors that influence the marketing strategy at Warung Bakso Titoti, find out the business position, find out alternative marketing strategies as well as priority strategies that Warung Bakso Titoti can choose during the Covid-19 pandemic. The method used in this research is a case study method with a qualitative descriptive approach. The analytical tools used are the IFE, EFE, IE, SWOT, and QSPM matrices. The results show that the main strengths and weaknesses are the good quality of raw materials and weak financial management. The main opportunities and threats are that there are still many marketing areas that have not been reached and the potential for the emergence of similar competitors is increasing. Titoti meatball shop business position is in cell I, namely in the growth and build position. The priority strategy that Warung Bakso Titoti can apply in marketing is to increase meatball product innovation in the face of competition.